Efficacy and cerebral mechanisms of acupuncture for chronic obstructive pulmonary disease: study protocol for a multicenter, randomized controlled neuroimaging trial - Chen, Xugui; Xiong, Chan; Xiao, Wei; Du, Longyi; Liu, Meilu; Yu, Yan; Liao, Chunyu; Zhang, Chengshun; Li, Yu; Mao, Bing; Fu, Juanjuan (Frontiers in Neurology, 2024)
Although acupuncture is recommended by chronic obstructive pulmonary disease (COPD) treatment guidelines owing to its effects on dyspnea, the underlying neurobiological mechanisms of these effects remain unclear. This study aims to evaluate the efficacy of acupuncture in patients with stable COPD and explore the possible involvement of specific brain regions. Methods: This is a multicenter, single-blind, randomized controlled trial. Ninety participants will be recruited from three centers and randomly assigned in a 1:1 ratio to undergo acupuncture at acupoints on the disease-affected meridian or non-acupoints on the non-affected meridian, in addition to routine pharmacological treatments. All participants will undergo 30 min of acupuncture three times a week for eight weeks and will be followed up for 12 months. The primary outcome will be the severity of dyspnea as measured using the Borg Dyspnea Scale and a visual analog scale at rest and after exercise. The secondary outcomes will include the multidimensional measurement of dyspnea using Dyspnea-12, the modified Medical Research Council Dyspnea Scale, and the COPD Assessment Test, quality of life assessments using St George's Respiratory Questionnaire and the Hospital Anxiety and Depression Scale, and additional measurements of exacerbation frequency, pulmonary function, and the 6-minute walking distance. Magnetic resonance imaging will be performed before and after exercise to explore the potential neurobiological mechanisms of exertional dyspnea. Anxiety and depression will be measured and analyzed for their correlation with the activation of specific brain areas involved in dyspnea. Discussion: This randomized controlled trial will conduct a multidimensional evaluation of the efficacy of acupuncture in relieving dyspnea in patients with COPD in terms of emotion and quality of life, and explore the neurobiological mechanisms underlying the effects of acupuncture on dyspnea from an imaging perspective. It is expected to provide strong evidence to support the use of acupuncture to relieve dyspnea in patients with COPD and in those with other diseases involving dyspnea, and provide novel insights into the central mechanisms of acupuncture intervention and dyspnea.